Internationalization in 2025 and Beyond: Taking It to the People - Rumbley, Laura (International Higher Education, 2025)
<h3 id="profound-cracks-are-emerging-in-the-social-and-political-orders-of-many-liberal-democracies-today-notably-in-the-united-states-and-europe-this-is-placing-internationalization-in-higher-education-under-unprecedented-pressure-strengthening-the-foundation-of-research-on-internationalizations-societal-impact-and-sharpening-the-approach-to-dissemination-of-research-findings-are-key-responses-to-this-watershed-moment" data-pm-slice="1 1 []">Profound cracks are emerging in the social and political orders of many liberal democracies today, notably in the United States and Europe. This is placing internationalization in higher education under unprecedented pressure. Strengthening the foundation of research on internationalization’s societal impact and sharpening the approach to dissemination of research findings are key responses to this watershed moment.